Diagnosen einer Zentralen Notaufnahme als Qualitätsindikator - Wilk, Florian; Grosse, F.; Liebel, J.; Wagner, M.; Dormann, H. (Notfall und Rettungsmedizin, 2019)
Background: Making the right diagnosis plays an important role in emergency departments, but objective indicators to investigate diagnostic quality are rarely available. Methods: By systematically comparing the main admission diagnosis (AD), the main discharge diagnosis (ED) and the main hospital diagnosis (HD), the diagnostic agreement (dÜ), -sensitivity (dSe), -specifity (dSp) and efficiency (dEff) were calculated for 28 time-critical diagnoses. Results: During the study period, 21,512 emergency department inpatients (average 63 years; min 0, max 104, standard deviation [SD] ± 21.4) were treated with 599 different main admission diagnoses. The diagnostic agreement (dÜ) and sensitivity (dSe) over all time-critical diagnoses reached 66.5 and 70.0%, the diagnostic specificity (dSp) 51.5%. The diagnostic sensitivity (dSe) was highest (100%) among patients with aortic aneurysm and dissection (dSp 72%). Inpatients with Intracranial injury reached the highest diagnostic specificity (dSp) of 94% (dSe 92%), while patients with vascular disorders of intestine had the largest gap between diagnostic sensitivity (dSe) and diagnostic specificity (dSp) (82 and 13%). The diagnostic efficiency over all emergency diagnoses (dEff) was 0.37/minute (min 0.03, max 92, SD ± 1.22), whereas the subgroup of patients with cardiac arrest reached highest diagnostic efficiency (dEff) of 1.04/minute (min 0.42, max 9.17, SD ± 1.41, dSe 55%). Conclusion: Quality indicators for time-critical diagnoses could be determined by routine data of the hospital information systems. By linking outcome- and process indicators diagnostic quality of an emergency department can be objectified.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Central emergency room; Diagnostic quality; Process optimization; Quality indicators; Quality management